Conceptual metaphor: its global and local aspects - Stanojević, Mateusz-Milan (Array, 2014)
Conceptual metaphor: its global and local aspects Mateusz-Milan Stanojević, University of Zagreb, Croatia One of the crucial claims about conceptual metaphor has been its capacity to organize conceptual structure. In one of their first studies into emotion concepts, Lakoff and Kövecses (1983) propose a central metaphor, ANGER IS A HOT FLUID IN A CONTAINER, as one of the organizational principles of the anger scenario. Still, later work on emotions (e.g. Kövecses 2000) showed that conceptual metaphor has a limited organizational role. In this paper we present the difference between comparable "globalist" and "localist" evidence, and show that it is a result of a different level of schematicity. This realization is a step towards integrating all the evidence into a single framework. "Globalist" evidence shows the centrality of metaphor in the organization of conceptual structure, discourse and grammar. In addition to the studies on emotions, other "globalist" evidence includes metaphor as the basis of cultural models in fiction and in everyday life (Turner 1996), politics (Lakoff 2002), etc. Metaphors have been put forward as a background mechanism regulating the production of metonymic expressions in newspaper texts (Brdar and Brdar-Szabó 2011). Schematic metaphors may be involved in grammar, e.g. in extensions towards epistemic meanings (e.g. Sweetser 1990) as well as in more recent views about the caused-motion construction of non-motion verbs (Baicchi 2011). In all these examples metaphor serves as the overall structural principle within a particular sphere. "Localist" evidence suggests that metaphors cannot play the role of an overall structural mechanism within a sphere or that there are other more basic mechanisms at play. For instance, Stanojević, Tralić and Ljubičić (2014) show that a number of diachronic, ecological and conceptual factors work alongside metaphor to determine the structure of the English concept of anger. Some authors claim that metaphors are metonymic in nature (e.g. Radden 2003), while others assert that the relation of conceptual autonomy and dependence may be used as a factor to determine metaphoricity of all grammatical constructions (Sullivan 2013). In more discursively-minded studies the deliberateness of metaphor (Steen 2008 ; Steen 2011) is claimed to play the decisive structural role. Overall, the "globalist" – "localist" distinction is based on varying levels of schematicity in defining metaphor and examining data. It implies (at least) a three-tiered view of metaphor as conceptual, linguistic and discursive (Steen 2007), which might be the way to integrate the diverse evidence into a single (more or less coherent) framework. References Baicchi, Annalisa. 2011. “Metaphoric motivation in grammatical structure: the caused-motion construction from the perspective of the lexical-constructional model.” In Motivation in Grammar and the Lexicon, edited by Klaus-Uwe Panther and Günter Radden, 149–69. Amsterdam, Philadelphia: John Benjamins. Brdar, Mario, and Rita Brdar-Szabó. 2011. “Metonymy, metaphor and the ‘weekend frame of mind.’” In Motivation in Grammar and the Lexicon, edited by Klaus-Uwe Panther and Günter Radden, 233–50. Amsterdam, Philadelphia: John Benjamins. Kövecses, Zoltán. 2000. Metaphor and Emotion: Language, Culture, and Body in Human Feeling. Studies in Emotion and Social Interaction. Cambridge, New York: Cambridge University Press. Lakoff, George. 2002. Moral Politics: How Liberals and Conservatives Think. 2nd ed. Chicago: University of Chicago Press. Lakoff, George, and Zoltán Kövecses. 1983. “The cognitive model of anger inherent in American English.” Cognitive Science Report 10. University of California at Berkeley, Berkeley, California: Cognitive Science Program, Institute of Cognitive Studies. Radden, Günter. 2003. “How metonymic are metaphors?” In Metaphor and Metonymy at the Crossroads: A Cognitive Perspective, edited by Antonio Barcelona, 93–108. Berlin ; New York: Mouton de Gruyter. Stanojević, Mateusz-Milan, Ivo Tralić, and Mateja Ljubičić. 2014. “Grammatical information and conceptual metaphors: the case of anger.” In Language as Information: Proceedings from the CALS Conference 2012, edited by Anita Peti-Stantić and Mateusz-Milan Stanojević, Peter Lang Edition, 131–54. Frankfurt am Main: Peter Lang. Steen, Gerard. 2007. Finding Metaphor in Grammar and Usage. Amsterdam, Philadelphia: John Benjamins. ———. 2008. “The paradox of metaphor: why we need a three-dimensional model of metaphor.” Metaphor and Symbol 23 (4): 213–41. ———. 2011. “What does really deliberate really mean?: More thoughts on metaphor and consciousness.” Metaphor and the Social World 1 (1): 53–56. doi:10.1075/msw.1.1.04ste. Sullivan, Karen. 2013. Frames and Constructions in Metaphoric Language. Amsterdam, Philadelphia: John Benjamins. Sweetser, Eve. 1990. From Etymology to Pragmatics: Metaphorical and Cultural Aspects of Semantic Structure. Cambridge: Cambridge University Press. Turner, Mark. 1996. The Literary Mind. New York: Oxford University Press.